Mosquito (Diptera: Culicidae) fauna in an area endemic for West Nile virus - Sebesta, O; Halouzka, J; Hubálek, Z; Juricová, Z; Rudolf, I; Sikutová, S; Svobodová, P; Reiter, P (Journal of vector ecology, 2010)
Mosquito collections with CDC light traps using dry ice and pigeon-baited traps were carried out in south Moravia (Czech Republic) from April to October in 2007 and 2008 at two study sites. In 2007, 11 two-day captures were carried out in two-week intervals, and 1,490 female mosquitoes of nine species were caught. In 2008, 15 two-day trappings of mosquitoes were carried out: 6,778 females of 22 species of mosquitoes were trapped. The results showed marked differences in abundance and species composition of mosquitoes between both study sites and between the trapping methods. In the floodplain forest ecosystem of the Soutok study area, Aedes vexans predominated. The species composition in the Nesyt study site was more varied and the most common species was Culex pipiens. At the latter study site, Anopheles hyrcanus (var. pseudopictus) and Uranotaenia unguiculata, mosquito species with largely southern Eurasian distribution, were repeatedly demonstrated. The largest capture of mosquitoes was in traps with CO2 placed at a height 1 m above the ground. The capture of mosquitoes in the pigeon-baited traps as well as in the traps with CO2 placed in the canopy of trees was markedly lower in both study sites, with the predominant species being Culex pipiens.
Keywords: Geography; Culicidae; Aedes; zeměpis; Animals; West Nile Fever; zvířata; západonilská horečka; Anopheles